Dissecting the Cytochrome P450 1A2‐ and 3A4‐Mediated Metabolism of Aflatoxin B1 in Ligand and Protein Contributions. Issue 12 (30th January 2017) - Bonomo, Silvia; Jørgensen, Flemming Steen; Olsen, Lars
Abstract: Aflatoxin B1 (AFB1) is a chemically intriguing compound because it has several potential sites of metabolism (SOMs), although only some of them are observed experimentally. Cytochrome P450 (CYP) 3A4 and 1A2 are the major isoforms involved in its metabolism. Here, we systematically investigate reactivity and accessibility of all possible SOMs in these two CYPs to elucidate AFB1 metabolism. DFT calculations were used to determine activation energies for each possible reaction. Aliphatic hydroxylation on position 9A and 3α are energetically favored, whereas position 9 is the preferred site for epoxidation. Docking studies, molecular dynamics (MD) simulations, and free energy (MM/GBSA) calculations were applied to elucidate the accessibility of each SOM. The most stable binding modes in CYP3A4 favor the formation of the 3α‐hydroxylated and 8, 9‐ exo ‐epoxide metabolites. Conversion of the methoxy group is also sterically possible, but not observed experimentally due to its low reactivity. In the CYP1A2 active site, AFB1 cannot orient position 3 towards the catalytic center, whereas the 8, 9‐ exo ‐epoxide and 9A‐hydroxylated metabolites are formed from the most stable and the 8, 9‐ endo ‐epoxide from a less stable binding mode, respectively. The results agree with experimental data and suggest that both reactivity and the shape of the enzyme active site need to be considered to understand the distribution of SOMs and to improve current SOM prediction methods. Abstract : SOMewhere : Combination of computational approaches to evaluate reactivity and accessibility in CYP1A2 and CYP3A4 for the different sites of metabolism (SOMs) of aflatoxin B1 reflect experimentally observed biotransformations.